Increasing participation by private physicians in the EPSDT Program in rural North Carolina. - Selby, M L (1992)
This study evaluated a method to increase physicians' participation in Early and Periodic Screening, Diagnosis and Treatment (EPSDT), a preventive health care program for Medicaid eligible children. Use of EPSDT can improve children's health status and reduce health care costs. Although the potential benefits of EPSDT are clear, the program is underused; low rates of participation by private physicians contribute to underuse. This study targeted a population of 73 primary care physicians in six rural counties in North Carolina where the physician supply, their participation in EPSDT, and use of EPSDT were low. A mailed intervention packet attempted to address barriers to participation perceived by private providers. The packet consisted of a carefully constructed letter, an informative journal article, and an educational pamphlet. Participation in EPSDT screening increased from 15 to 25 private physicians (67 percent), at a cost, on average, of less than $30 per recruited provider. Suggestions are presented for adapting the intervention packet to other settings.